2013
DOI: 10.1016/j.atmosenv.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in the Industrial Heartland of Alberta, Canada and potential impacts on human health

Abstract: The “Industrial Heartland” of Alberta is Canada’s largest hydrocarbon processing center, with more than 40 major chemical, petrochemical, and oil and gas facilities. Emissions from these industries affect local air quality and human health. This paper characterizes ambient levels of 77 volatile organic compounds (VOCs) in the region using high-precision measurements collected in summer 2010. Remarkably strong enhancements of 43 VOCs were detected, and concentrations in the industrial plumes were often similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Long-term continuous monitoring of air quality in locations near industrial facilities, including petroleum refineries, is generally scarce, and few studies on long-term pollutant concentrations have been published in the peer-reviewed literature to date [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term continuous monitoring of air quality in locations near industrial facilities, including petroleum refineries, is generally scarce, and few studies on long-term pollutant concentrations have been published in the peer-reviewed literature to date [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple monitoring studies have been conducted near petroleum refineries, these studies were usually limited in temporal coverage, spanning periods from hours to a few months, with some exceptions including seasonal sampling over longer periods of time [3][4][5][6][7][8]. Previous work on air quality at refinery perimeters primarily focused on monitoring multiple volatile organic compounds (VOCs), with more limited emphasis on measurements of particulate matter (PM), trace gases, metals, and polycyclic aromatic hydrocarbons (PAHs) [2,3,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…due to climate mitigation and human mortality) can be significantly high and should be taken into account during decision making [1] . Several studies have been conducted around the world that investigate the air quality in industrial areas in terms of various pollutants such as volatile organic compounds [2] , trace elements [3] , air pollution indices (including SO 2 , NO 2 , PM 10 ) [4] and others. Some of these studies have attempted to predict future air pollution levels through detailed monitoring [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The results of a monitoring program conducted at the LYPIC indicated that maximum levels of a known human carcinogen, benzene, were as high as 618 ppbv during the day (Lin et al, 2004). Another study in Alberta, Canada showed that 1,3-butadiene, another known human carcinogen, was measured at 27 ppbv downwind of an industrial area of more than 40 companies, including chemical, petrochemical, and oil and gas facilities (Simpson et al, 2013). These results indicate that emissions of VOCs from petroleum refineries and petrochemical plants have a significant impact on surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…VOCs in ambient air are an increasing concern because many of them have been identified to be human carcinogens (Simpson et al, 2013). Occupational epidemiological studies of workers at petrochemical and refinery plants indicate that exposure to benzene has a dose-response relationship with the risk for acute non-lymphocytic/acute myelogenous leukemia (Bloemen et al, 2004;Gun et al, 2006;Kirkeleit et al, 2008), exposure to vinyl chloride is associated with a substantial excess of angiosarcoma of the liver (Mundt et al, 2000;Ward et al, 2001), and exposure to butadiene is associated with an increased risk of non-Hodgkin lymphoma (Divine and Hartman, 2001).…”
Section: Introductionmentioning
confidence: 99%